Determinan Perilaku Konsumen terhadap Pembelian Buah Pisang Ambon (Musa paradisiaca var. Sapientum (l.) Kunt.) di Jakarta Selatan Saat Pandemi Covid-19 - Rahel, Gabe Nur; Budiaji, Weksi; Mulyati, Sri; Bukhari, Ahmad; Mursyidah, Himmatul; Abdullah, Syarif; Sholihin, Miftahus; Wijaya, Ferdian Bangkit (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to determine the variables that influence consumer behavior in purchasing decisions in buying bananas at Toko Tani Indonesia Center Pasar Minggu. This study was conducted from October 2021 to June 2022. The sampling technique used in this study was accidental sampling, with the number of respondents as many as 40. The independent variables in this study suffered from a multicollinearity problem. One method to overcome this is applying the regression of Least Absolute Shrinkage and Selection Operator (LASSO). LASSO regression can solve the problem of multicollinearity by shrinking the estimated coefficients towards zero or setting them to exactly zero so that LASSO regression can select variables in the regression model. The result of the LASSO analysis, variables that had a significant influence on consumers' decision to buy bananas were physiological factors, i.e., motivation, perception, knowledge, belief, and attitude.